2016
DOI: 10.1007/s10719-016-9671-5
|View full text |Cite
|
Sign up to set email alerts
|

Housekeeping promoter 5’pcmah-2 of pig CMP-N-acetylneuraminic acid hydroxylase gene for NeuGc expression

Abstract: In the present study, we isolated pCMAH house-keeping promoter regions (Ph), which are responsible for transcriptional regulation and which are located upstream of the alternative transcript pcmah-2. Luciferase reporter assays using serial construction of each deleted promoter demonstrated that the Ph promoter was highly active in pig-derived kidney PK15. Ph promoter of pcmah lacked a TATA box, but contained three putative Sp1 binding sites. Mutations of these Sp1 binding sites always resulted in the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 28 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Previously, we demonstrated that the pig cmah gene has two distinct 5′ alternative splicing forms, 5′pcmah-1 and 5′pcmah-2 , which exhibit intestine-specific and housekeeping expression, respectively [ 14 ] ( Figure 2 a). Given our previous finding that 5′pcmah-1 and 5′pcmah-2 encode an identical pCMAH protein [ 15 ] ( Figure 2 a), we questioned which transcript is responsible for the loss of CMAH protein following LPS treatment in IPI-2I cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we demonstrated that the pig cmah gene has two distinct 5′ alternative splicing forms, 5′pcmah-1 and 5′pcmah-2 , which exhibit intestine-specific and housekeeping expression, respectively [ 14 ] ( Figure 2 a). Given our previous finding that 5′pcmah-1 and 5′pcmah-2 encode an identical pCMAH protein [ 15 ] ( Figure 2 a), we questioned which transcript is responsible for the loss of CMAH protein following LPS treatment in IPI-2I cells.…”
Section: Resultsmentioning
confidence: 99%
“…We next attempted to elucidate the underlying mechanism responsible for transcriptional loss of 5′pcmah-1 following LPS exposure. Since 5′pcmah-1 is mainly controlled by the Pi (intestine-specific) promoter [ 14 , 16 ], we examined the effects of LPS treatment on Pi promoter activity using serially constructed 5′-deletion mutants, Pi-700, Pi-542, Pi-260 and Pi-233. The activity of Pi-542 and Pi-700 was markedly decreased upon LPS treatment in IPI-2I cells, while there was no alteration in the activity of Pi-260 or Pi-230 after LPS treatment ( Figure 2 c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations